O Coletivo de acompanhamento político pedagógico - CAPP nos cursos do Pronera: o caso do curso de enfermagem com ênfase em Saúde Pública na Unioeste, Campus Foz do Iguaçu - Rodrigues, Sandra Marli da Rocha (2025)
This research aims to analyze the role of the Political Pedagogical Monitoring Collective (CAPP) in practice, in the first Nursing Course with Emphasis on Public Health, through the National Program for Education in Land Reform (Pronera), at Unioeste – Foz do Iguaçu Campus. The central research question is: What is the relevance of the CAPP in Pronera courses? The general objective of the research was to understand the importance of the CAPP in the organizational and collective process within Pronera courses, from the perspective of human development, beyond the technical/scientific training of rural students. The specific objectives were: to understand the pedagogy of the Landless Workers Movement (MST) in the struggles for land and the struggles of the Rural Education Movement; to analyze Pronera as a public policy and its organizational structure; to highlight the importance of the CAPP in Pronera courses; and to demonstrate the role of the CAPP in the Nursing Course with Emphasis on Public Health. The methodology used was a Case Study, starting with a literature review, followed by field research. The hypothesis, confirmed in the field research and which became the thesis defended here, was that: The CAPP is essential for the development of human formation integrated with technical and scientific education in Pronera courses. The study presented the formative matrices of the collective Sem Terra subject, which are: social struggle, collective organization, work, culture, and history. The study showed that the emergence of the Movement for Rural Education was linked to political, economic, social, and cultural struggles. It is concluded that Pronera is the result of the struggles for land and rural education, and this important public policy paved the way for other rural education policies. It was found that the CAPP is indispensable in Pronera courses because neither higher education institutions (IES) nor INCRA have the physical structure or human resources trained to meet the demands of these courses in an alternating regime. The study showed that the CAPP plays a central political and pedagogical role in Pronera courses. Regarding the Nursing Course with Emphasis on Public Health, the study demonstrated that the CAPP acts as the link between all the entities involved in the course and in dialogue with partners in course execution. It also showed that the formative dimensions proposed for Pronera courses are realized because there is a CAPP conducting political and pedagogical work in the daily routine of the course and which went beyond the functions described in the analyzed documents.